Characteristics of resistant starch in water chestnut flour as improved by preconditioning process. Issue 1 (1st January 2019) - Hussain, Syed Zameer; Beigh, Mushtaq Ahmed; Naseer, Bazila; Amin, Tawheed; Naik, Haroon Rashid
ABSTRACT: Before cracking, subjecting water chestnuts to pre-conditioning is a common practice. However, the existing practice of pre-conditioning has no scientific rationale and therefore leads to low flour recovery and poor quality. Thus, the aim of the present research work was to optimize the pre-conditioning process for water chestnuts and to analyze the efficacy of optimized process as a means to increase the resistant starch content and reduce the glycemic index in water chestnut flour. Central composite rotatable design was used to determine the effect of water chestnut:water ratio, water temperature and pre-conditioning time on yield and brightness (L* value) of flour. Optimization of pre-conditioning process was done by response surface of desirability function. Regression models for both the product responses were highly significant ( p < 0.0001) with high coefficient of determination ( R 2 > 0.95). Scanning electron microscopy (SEM) showed compact, smooth and oval shaped starch granules with crystalline network in preconditioned water chestnut flour. FTIR studies also indicated higher absorbance ratio of 1047/1022 cm −1 for preconditioned water chestnut flour which further authenticated the SEM findings. Subjecting water chestnuts to optimized conditions of pre-conditioning (i.e., water chestnut:water ratio 1:1.5; water temperature 87.85̊C and pre-condition time 45 min), also increased the resistant starch content and lowered the glycemic index and glycemic load of the water chestnut flour.